Kinetika Penyerapan Air pada Beras - Chatarina Wariyah; Chairil Anwar; Mary Astuti; Supriyadi Supriyadi (agriTECH, 2007)
Water absorption rate of three different rice, i.e. low, medium and high amylose content rice, were evaluated based on their kinetic reactions. Water absorption kinetics were determined at below (28, 50, 60 and 70 oC) and above (80, 90 and 100 oC) gelatinization temperatures. Reaction rate constant was evaluated from the curve of relation between moisture content and soaking time, and activation energy was calculated with Arrhenius equation. The results showed that water absorption at below gelatinization temperature followed first order reaction, while at above gelatinization temperature reaction followed with zero order. Rice with high amylose content tended to absorb water easier than low amylose one at temperature less than 70 oC, however, it was vice versa at temperature above 70 oC. Activation energy of water absorption below the gelatinization temperature was lower than above gelatinization temperature.ABSTRAKKecepatan absorpsi air dari beras amilosa rendah, sedang dan tinggi, dievaluasi berdasarkan kinetika reaksinya. Kinetika absorpsi air ditentukan pada suhu di bawah gelatinisasi (28, 50, 60 dan 70 oC ) dan pada suhu di atas gela- tinisasi (80, 90, 100 oC). Konstanta kecepatan reaksi ditentukan dengan mengevaluasi grafik hubungan antara kadar air dan lama perendaman, dan energi aktivasi dihitung dengan persamaan Arrhenius. Hasil penelitian menunjukkan absorpsi air di bawah suhu gelatinisasi mengikuti reaksi orde satu, sedangkan pada suhu gelatinisasi mengikuti reaksi orde nol. Beras dengan amilosa tinggi relatif lebih mudah menyerap air dibandingkan beras amilosa rendah pada suhu kurang dari 70 oC, namun pada suhu lebih dari 70 oC absorpsi air menjadi lebih kecil. Energi aktivasi absorpsi air pada suhu di bawah gelatinisasi lebih rendah dibandingkan pada suhu gelatinisasi.